THE INFLUENCE OF PERCEPTION ABOUT PRODUCT ADVERTORIAL IN NEWSPAPER TOWARD CONSUMER ATTITUDE - Rika Melati; Basu Swastha Dharmmestha (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The purpose of this research is to analysis the influence of perception about health product advertorial towardconsumer attitude. Advertorial is advertising looks like news as its editorial format. The purpose of advertising is toinfluence consumer buying behavior. Consumer attitude is one of predictor to determine consumer behavior.Method of this research is survey which GMU student that have read advertorial of healt product in newspaperas population. Method of sampling use purposive sampling. There are 3 variables in this research: perception of health product advertorial as independent variable while cognitive and affective response as dependent variables. All variables are measured using Likert scale. The primary data collected using questionnaires that given to 170respondents. Validity and reliability of research instrument were tested using Confirmatory Factor Analysis andAlpha Cronbach’s. All hypotheses tested by using Linear Regression. The finding of this research shown that perception of health product advertorial significantly influence cognitiveand affective of consumer response . The influence perception of health product advertorial toward cognitive responseof GMU student that read newpaper is 21,3% and the influence of health product advertorial toward affective responseof GMU student that read newspaper is 8,7%. Another factors estimated influencing attitude toward the advertorialare individual education, attitude toward the brand previously, dan level of individual involvement. Keyword: Advertorial, attitude, perception, student of Gadjah Mada University